The Effects of Overconfidence and Risk Perception on Generation Z Stock Investment Decisions: The Moderating Role of Financial Literacy - Maureen Lucia Bernadette Pandelaki; Kenneth August Sahetapy; Novie P. Sibilang (Economics and Digital Business Review, 2026)
This study aims to examine the effects of overconfidence and risk perception on the stock investment decisions of Generation Z and to investigate whether financial literacy moderates these relationships. A quantitative research method was used using logistic regression analysis. A total of 212 Generation Z respondents from Universitas Klabat in Indonesia were selected through purposive sampling. The findings indicate that overconfidence does not have a significant effect on investment decisions, while risk perception has a positive effect on investment decisions. Furthermore, financial literacy does not moderate the relationship between overconfidence and investment decisions, however, it does moderate the relationship between risk perception and investment decisions. This study contributes to the financial literature by demonstrating the roles of behavioural biases and financial knowledge in influencing the investment decisions of Generation Z.